Survival of endodontically treated permanent teeth among children: a retrospective cohort study - Saitah Bufersen; Judith Jones; Jayapriyaa Shanmugham; Tun-Yi Hsu; Sharron Rich; Ali H. Ziyab; Sami Chogle (BMC, 2021)
Abstract Background Outcome studies of nonsurgical root canal treatment (NSRCT) in permanent teeth of children are scarce. This study investigated survival and assessed the variables associated with failure of endodontically treated teeth (ETT) in 6- to 18-year-olds. Methods Records of subjects who received NSRCT at age 6-18 years at Boston University between 2007 and 2015 were assessed for the occurrence of untoward events. Kaplan-Meier survival curves were used to investigate the survival of ETT in the total sample. Adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) were estimated. Results The analysis included 341 patients (424 ETT). Kaplan-Meier survival curves differed according to age at treatment (log-rank P = 0.026), with survival being the lowest among the youngest age group. The estimated 5-year survival probability was 80% for 15- to 18-year-olds, 64.8% for 12- to 14-year-olds and 46.4% for 6- to 11-year-olds. Compared to age at treatment of 15-18 years, age at treatment of 6-11 years (aHR: 2.19, 95% CI 1.02-4.67) and 12-14 years (aHR: 2.02, 95% CI 1.15-3.55) was associated with an increased risk of ETT failure. In the total study sample, the estimated cumulative survival probability was 93.3% at 12 months, 88.0% at 24 months, 76.2% at 36 months, 71.0% at 48 months, and 69.1% at 60 months. Conclusions In children, ETT are more likely to survive when NSRCTs are performed at an older age.